Peranan Subsektor Kehutanan dalam Pembangunan Wilayah Provinsi Jawa Barat: Pendekatan Input-Output dan Pewilayahan - Desli Triman Zendrato; Ernan Rustiadi; Omo Rusdiana (P4W LPPM IPB, 2020)
The Role of the Forestry Subsector in the Regional Development of West Java Province: Input-Output and Clustering Approach West Java Province has a problem to balance economic growth, population welfare, and environmental sustainability. Land requirements to support economic activities have caused land conversion and land use misalignment that are not in line with their function and carrying capacity. This research is aimed to analyze the role of the forestry subsector within the regional economy, how the alignments between forest area use and spatial planning, and to analyze regional typology based on environment carrying capacity based on ecosystem services. Research methods used in this research include Input-Output Analysis, Spatial Analysis, Principal Component Analysis (PCA), and Spatial Clustering Analysis. Results of the alignment analysis between land use/land cover and spatial planning showed that about 20.8% or 167,473 ha of forest area experienced land use/land cover changes. Results of the Input-Output analysis showed that the role of the forestry subsector in using outputs from other sectors and providing outputs for other sectors were low. West Java Province can be divided into 4 clusters: center of paddy production, regions that are dominated by forest, densely populated regions, and drought-prone regions.